Zawieszenie zwrotu kosztów opieki zdrowotnej a dyrektywa transgraniczna - Lenio, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This paper outlines the possibility of adjournment of health care costs refund in the light of the cross-border health care directive. The main purpose of this paper is to determine whether cross-border health care Directive has been correctly implemented in the national law. The Directive permits adjournment of refund of cross-border health care costs. It seems that the Directive is not properly implemented into the polish law. The controversy surrounds the act of tying reimbursements to a strict budget in the National Health Fund.
Keywords: opieka zdrowotna; dyrektywa transgraniczna; ochrona zdrowia